(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
The aim of this work was to improve fluconazole flowability by wet granulation and to study the effect of granulation on drug dissolution from tablets and capsules. Fluconazole was submitted to a process of wet granulation in a high-speed granulator using Plasdone® K29/32 or K90. Flow properties of granules and dissolution profiles for tablets and capsules produced with them were determined. Fluconazole granules demonstrated better flowability, calculated by angle of repose and compressibility index data, compared with powder. Additionally, it was observed that the granulation process improved the dissolution efficiency (ED) of fluconazole from tablets and capsules, which could also suggest an increase in bioavailability. Higher dissolution efficiencies were achieved with Plasdone® K29/32.